1991
DOI: 10.1152/jn.1991.65.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar dysmetria at the elbow, wrist, and fingers

Abstract: 1. The objective was to investigate in cerebellar patients with dysmetria the kinematic and electromyographic (EMG) characteristics of large and small movements at the elbow, wrist, and finger and thereby to determine the nature of cerebellar dysmetria at distal as well as proximal joints. Flexions were made as fast as possible by moving relatively heavy manipulanda for each joint to the same end position through 5, 30, and 60 degrees. 2. In normal subjects flexions at all joints were accompanied by similar tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(151 citation statements)
references
References 0 publications
10
140
0
1
Order By: Relevance
“…This fits the clinical finding that mainly rapid movements are impaired in patients with cerebellar lesions (Hore et al, 1991;Berardelli et al, 1996). Several authors (Ivry and Keele, 1989;Jueptner et al, 1995;Tesche and Karhu, 2000;Dreher and Grafman, 2002;Ivry et al, 2002) have suggested a timing function for the cerebellum.…”
Section: Role and Organization Of The Cerebellumsupporting
confidence: 88%
“…This fits the clinical finding that mainly rapid movements are impaired in patients with cerebellar lesions (Hore et al, 1991;Berardelli et al, 1996). Several authors (Ivry and Keele, 1989;Jueptner et al, 1995;Tesche and Karhu, 2000;Dreher and Grafman, 2002;Ivry et al, 2002) have suggested a timing function for the cerebellum.…”
Section: Role and Organization Of The Cerebellumsupporting
confidence: 88%
“…Because the durations relevant for movement (for instance in muscle phasing and coordination) fall within the sub-second range (Hore et al, 1991), it has been suggested these short intervals may be measured within the motor system. Observation that cerebellar lesions can lead to deficits in movement-related timing (Ivry & Keele, 1989;Ivry, Keele, & Diener, 1988) and in non-motor timing at the milliseconds range (Casini & Ivry, 1999) have combined to implicate this structure as a candidate locus for such processes (Ivry, 1996(Ivry, , 1997, but see also (Gibbon et al, 1997).…”
Section: Activity Greater During the 06 S Intervalmentioning
confidence: 99%
“…The measurement of tens or hundreds of milliseconds is important for coordination of muscles during movement (Hore, Wild, & Diener, 1991), while the measurement of multisecond durations is more commonly associated with learned behaviours such as social interaction or foraging (Brunner, Kacelnik, & Gibbon, 1992;Pyke, Pulliam, & Charnov, 1977). Time measurement has also been shown to have quite different properties at these two duration ranges.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that synchronous CS activity may facilitate the timing of muscle activation (Llinás 1991), and damage to the cerebellum or IO leads to a variety of motor symptoms, including action tremors, which may be related to the improperly timed activation of muscles (Adams and Victor 1993;Holmes 1939;Hore et al 1991;Soechting et al 1976). Moreover, the patterns of synchronous CS activity have been shown to change in relation to voluntary movements (Welsh et al 1995).…”
Section: Possible Relevance To Action Tremormentioning
confidence: 99%